2017
DOI: 10.1177/0164027516681050
|View full text |Cite
|
Sign up to set email alerts
|

Types of Family Caregiving and Daily Experiences in Midlife and Late Adulthood: The Moderating Influences of Marital Status and Age

Abstract: Guided by the life-course perspective, this study contributes to the family caregiving, aging, and disability literature by examining the daily experiences of three types of family caregivers in midlife and late adulthood. A sample of 162 caregivers from the National Survey of Midlife in the United States study completed interviews, questionnaires, and a Daily Diary Study. Multilevel models showed the patterns of daily time use did not differ by caregiver types. Caregivers of sons/daughters with developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[26] Parents are the most common caregivers of patients with developmental disabilities. [27] The high representation of parents among caregivers in this study had an impact on the distribution of some of their characteristics—caregivers were more likely to be older, officially married, or common-law partnered. A similar study conducted by Marcon et al [15] also found that caregivers are, on average, older and more likely to be living with a partner.…”
Section: Discussionmentioning
confidence: 97%
“…[26] Parents are the most common caregivers of patients with developmental disabilities. [27] The high representation of parents among caregivers in this study had an impact on the distribution of some of their characteristics—caregivers were more likely to be older, officially married, or common-law partnered. A similar study conducted by Marcon et al [15] also found that caregivers are, on average, older and more likely to be living with a partner.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Kim and Yoon (2020) found that sleep quality can be an important compensatory pathway that protects against inflammation, and sleep quality can also be impacted by caregiving stress (Gao et al, 2019). Social factors such as marital quality (Wong & Shobo, 2017) and other roles that might either elicit stress or provide resources, such as parenting and employment (Barnett, 2015) are also potentially involved in affecting the health trajectories of caregiving. Future studies including such contextual factors alongside our latent variable approaches for assessing inflammation should be further illuminating.…”
Section: Discussionmentioning
confidence: 99%
“…14 Other studies have documented differences in caregivers' daily emotional health and stressors by care-recipient characteristics and engagement level. [15][16][17][18] Yet, emotional health has not been compared systematically for caregivers who are assisting older adults with dementia and those assisting for other reasons. Moreover, investigations into the emotional implications of different types of care time, and how they may differ when the care recipient is living with dementia, are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…found relative to non‐caregivers, worse emotional health among caregivers to older adults 14 . Other studies have documented differences in caregivers’ daily emotional health and stressors by care‐recipient characteristics and engagement level 15–18 . Yet, emotional health has not been compared systematically for caregivers who are assisting older adults with dementia and those assisting for other reasons.…”
Section: Introductionmentioning
confidence: 99%